Activating de novo mutations in NFE2L2 encoding NRF2 cause a multisystem disorder. Issue 1 (December 2017) - Huppke, Peter; Weissbach, Susann; Church, Joseph; Schnur, Rhonda; Krusen, Martina; Dreha-Kulaczewski, Steffi; Kühn-Velten, W. Nikolaus; Wolf, Annika; Huppke, Brenda; Millan, Francisca; Begtrup, Amber; Almusafri, Fatima; et al.
Abstract Transcription factor NRF2, encoded byNFE2L2, is the master regulator of defense against stress in mammalian cells. Somatic mutations ofNFE2L2 leading to NRF2 accumulation promote cell survival and drug resistance in cancer cells. Here we show that the same mutations as inborn de novo mutations cause an early onset multisystem disorder with failure to thrive, immunodeficiency and neurological symptoms. NRF2 accumulation leads to widespread misregulation of gene expression and an imbalance in cytosolic redox balance. The unique combination of white matter lesions, hypohomocysteinaemia and increased G-6-P-dehydrogenase activity will facilitate early diagnosis and therapeutic intervention of this novel disorder. The NRF2 transcription factor regulates the response to stress in mammalian cells. Here, the authors show that activating mutations in NRF2, commonly found in cancer cells, are found in four patients with a multisystem disorder characterized by immunodeficiency and neurological symptoms.